The effectiveness of gratitude intervention in reducing negative emotions in sexual abuse victims - Hamka, Hamka; Suen, Mein-Woei; Anganthi, Nisa Rachmah Nur; Haq, Aniq Hudiyah Bil; Prasetyo, Bayu (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2023)
Gratitude therapy is a positive psychotherapy approach given to victims of sexual abuse to generate positive thinking by expressing gratitude to the environment, God and other people. This research aims to test gratitude intervention as a religious activity undertaken to reduce negative emotions in victims of sexual abuse. A total of 104 such victims were identified using the snowball sampling method who were divided into an experimental group (N=52) and a control group (N=52). They were diagnosed as having negative emotions based on the child Trauma Questionnaire Shot-Focus (CTQ-SF) and Gratitude Questioner-6 (GQ-6) with triple ANOVA data analysis. The study’s results demonstrate a significant influence of gratitude on negative emotion, with values of F(39,037) = 4.71, p < .01, and ηp2 = 0.113. It can increase feelings of gratitude and reduce negative emotions in victims of sexual abuse. Gratitude therapy helps reduce negative emotions and foster positive emotions amongst such victims. The study could be implemented in people who experience negative emotions related to clinical and non-clinical disorders.